Exploring the Potential of AI Tools in Education: A Thematic Analysis of Gemini.ai - Supriyadi, Edi; Pahmi, Samsul (Universitas Wiralodra, 2024)
Artificial intelligence (AI) technologies, such as Gemini.ai, are revolutionizing higher education by enhancing data analysis and interpretation. This study aimed to investigate how Gemini.ai can enhance clarity in analytical results, provide contextually adaptive responses, and excel in advanced data modeling. We collected data through interviews with industrial engineering students and conducted thematic analysis using a qualitative research approach. The findings reveal that Gemini.ai significantly enhances user comprehension by simplifying complex data, offering tailored responses based on user commands, and integrating external information sources for robust data modeling. However, the study also highlights the need for further development, including improved customization options and advanced modeling features. These results demonstrate the transformative potential of AI tools like Gemini.ai in fostering intuitive, user-centric analytical experiences. The insights gained can inform the development of AI-driven educational tools, promoting personalized learning and critical thinking in higher education. Future research should explore interdisciplinary applications and the ethical implications of integrating AI in education to enhance its efficacy and accessibility.